A stakeholder-based confirmatory factor analysis of a smartwatch innovation management model for holistic older adult health care in Thailand - Phromsen, Methee; Sukkamart, Aukkapong; Siripongdee, Surapong (Edelweiss Applied Science and Technology, 2026)
Thailand’s transition to a super-aged society requires innovative management frameworks to support technology-enabled healthcare for older adults. Smartwatches offer significant potential for continuous health monitoring. However, a validated management model suitable for Thailand’s healthcare context remains underdeveloped. Therefore, this study developed and validated a second-order confirmatory factor analysis (CFA) of smartwatch innovation management factors for holistic older adult care, grounded in stakeholder perspectives. A cross-sectional survey was conducted with 260 stakeholders involved in a smartwatch-based elderly care pilot project in Thailand’s northern Chiang Rai Province. Participants included physicians, nurses, village health volunteers, and caregivers. Data were collected using a five-point Likert-scale questionnaire comprising 13 observed variables across four proposed components. These included Health Data Management (HMS1), Holistic Health Integration (HMS2), Connection with Healthcare Services (HMS3), and Technology Design Suitability for Older Adults (HMS4). LISREL was used to conduct the CFA, which assessed construct validity. The second-order model demonstrated excellent fit (χ² = 2.54, df = 6, p = 0.952, χ²/df = 0.42, RMSEA = 0.00, CFI = 0.99, GFI = 0.98). All first- and second-order factor loadings were statistically significant (p < .01). HMS4 (β = 0.95) and HMS3 (β = 0.94) emerged as the most influential dimensions. Construct reliability and convergent validity were confirmed (CR ≥ 0.75; AVE ≥ 0.50). The findings indicate that effective smartwatch innovation management for older adults must prioritize age-appropriate technology design and integration with formal healthcare systems. The validated framework provides policy and implementation guidance grounded in professional stakeholder assessment.